(untitled) (Fiep Bulletin - online, 2014)
The aim of the work is the evaluation of the quality of life in the relationship to level of physical activity of students CPU in Nitra. The research file was made of 424 students with specializations of Teacher training study programmes. The collection of the data was provided by questionnaire method. The relationship between the level of sport activity and the areas of life quality was evaluated by using correlation analysis. The results show differentiated relationship between the level of sport activity and importance, which the students attribute to different areas of life quality. By students with low (2.61 ± 1.07 per week) and high frequency (5.52 ± 0.63 per week) of physical activity were not noticed important relationships with satisfaction in particular areas of life quality. The satisfaction with life quality was found out by the students with average physical activity (3.76 ± 1.05 per week) in areas of physical (p<0.05), spiritual (0.01) and material comfortance (p<0.05), let us say, with the free time (p<0.10) and also in consideration of material possession (p<0.10). It turns out, that the occasional physical activity significantly affects the life quality of the students CPU in N itra in most of its areas. Aknowledgment: This article is a part of grant MŠ KE GA 014UKF -4/2013 with name “Improving the quality and the level of health of adolescent with means of motor activities at primary and secondary schools”. It’s realized at the Department of Physical Education and Sport in Faculty of Education at Constantine the Philosopher University during 2013 – 2015.